Women's employment status in Indonesia: An intersectionality perspective on disability, household responsibilities, and socioeconomic factors - Putri Meliza Sari; Rowiyah Asengbaramae; Egi Kurniawan (An-Nisa’ Journal of Gender Studies, 2026)
Women’s employment in Indonesia continues to be characterized by persistent inequalities influenced by disability, household responsibilities, socioeconomic resources, and spatial location. This study investigates women’s economic empowerment through inclusive employment by analyzing the associations between disability status, household characteristics, and socioeconomic factors and women’s employment status in Indonesia. Drawing on data from the 2021 Indonesian National Labor Force Survey (Sakernas), which includes 207,276 working-age women, the research adopts an intersectional perspective and uses multinomial logistic regression to examine these relationships. The results indicate that women with disabilities are less likely to obtain salaried employment and are more frequently found in self-employment and unpaid family work, suggesting limited access to formal and protected employment. Household headship and high household workload are associated with greater vulnerability to less secure employment, underscoring the ongoing impact of unpaid domestic responsibilities. Conversely, higher levels of education and digital technology enhance women’s access to formal, secure employment, whereas rural residence is associated with a greater likelihood of informal, agricultural-based work. The study concludes that women’s employment status is shaped by the intersection of disability status, household characteristics, socioeconomic resources, digital technology use, and place of residence. These findings contribute to the intersectionality perspective by demonstrating that employment status reflects access to decent work. The study further supports the development of gender-responsive and disability-inclusive labor policies by emphasizing the importance of improved accessibility, digital literacy, social protection, and expanded employment opportunities in rural areas.